How Do Transformational Leaders Promote Exploratory and Exploitative Innovation? Examining the Black Box through MASEM1. Issue 6 (22nd August 2016) - S. Kraft, Priscilla; Bausch, Andreas
Abstract : Understanding how firms can promote exploratory and exploitative innovations is of high interest for both scholars and practitioners. Although a substantial body of research has emphasized that top management's transformational leadership is crucial to innovation, the mechanisms through which strategic leaders influence these distinct types of innovations remain unclear. Building on upper echelon and social learning theory, this study develops and empirically examines a model that investigates the mediating roles of three distinct strategic orientations (market, learning, and entrepreneurial orientation) on the relationship between transformational leadership and exploratory and exploitative innovation. Using meta‐analytic methods combined with structural equation modeling, this study integrates findings from separate research streams, covering over 15 years of research, and using a sample of 215 effect sizes from 75 studies. The results from the partial mediation model reveal that transformational leaders play a key role in creating these specific strategic orientations which, in turn, support different innovation outcomes. Specifically, the findings indicate that transformational leaders promote exploitative innovations predominantly by building a market orientation, whereas they foster exploratory innovations by stimulating an entrepreneurial and a learning orientation. Hence, this study extends upper echelon research by uncovering the different mechanisms through which transformational leaders promote exploratory and exploitative innovations as it theoretically identifies and empirically validates the unique mediating roles of three specific strategic orientations. The results thus provide valuable insights for the challenging management of exploratory and exploitative innovations, as they provide a "guiding map" which reveals how transformational leaders from the top may use specific orientations to foster these distinct types of innovations.